Programming the Mobile Web - Firtman, Maximiliano (Cambridge : O'Reilly Media, Incorporated LaVergne : Ingram Publisher Services [Distributor], 2010)
Annotation Today's market for mobile apps goes beyond the iPhone to include BlackBerry, Nokia, Windows Phone, and smartphones powered by Android, webOS, and other platforms. If you're an experienced web developer, this book shows you how to build a standard app core that you can extend to work with specific devices. You'll learn the particulars and pitfalls of building mobile apps with HTML, CSS, and other standard web tools.You'll also explore platform variations, finicky mobile browsers, Ajax design patterns for mobile, and much more. Before you know it, you'll be able to create mashups using Web 2.0 APIs in apps for the App Store, App World, OVI Store, Android Market, and other online retailers.Learn how to use your existing web skills to move into mobile developmentDiscover key differences in mobile app design and navigation, including touch devicesUse HTML, CSS, JavaScript, and Ajax to create effective user interfaces in the mobile environmentLearn about technologies such as HTML5, XHTML MP, and WebKit extensionsUnderstand variations of platforms such as Symbian, BlackBerry, webOS, Bada, Android, and iOS for iPhone and iPadBypass the browser to create offline apps and widgets using web technologies
Scholarly & Professional